Influence of Infill Wall Configuration on Failure Modes of RC Frames - Xiaojie Zhou; Xiaoyuan Kou; Quanmin Peng; Jintao Cui (Shock and Vibration)
An improper configuration of masonry infill walls in RC frame may lead to short column effect on the columns, which is harmful to the seismic behavior of the structure. In this study, a bare frame and two single-story, single-bay RC frames, partially infilled with masonry, were tested under cyclic loading. The failure mechanism and seismic performance of these partially infilled RC frames (with an infill height of 600 mm) with different types of connections were analysed. Based on the experiment, nonlinear finite element simulation and analysis were conducted to study the effects of the infill walls and connections. The results show that both mechanical performance and failure mode are affected by the infill height, the type of connection between the frame and the infill, and the ratio of shear bearing capacity of the frame column to that of the infill. For the masonry-infilled frame with rigid connection, the higher the infill wall is, the lower the shear bearing capacity ratio will be. Thus, the effect of the lateral constraint of the infill wall on the column increases, and the shear span ratio of the free segment of the column decreases, resulting in the short column effect. Based on the analysis results, a value of 2.0 is suggested for the critical shear bearing capacity ratio of the frame column to the infill wall. If the shear bearing capacity ratio is less than 2.0 and the shear span ratio of the column free segment is not more than 2.0, the short column effect will occur. For the infilled frame with flexible connection, both the lateral constraint from the wall to the column and the wall-frame interaction decrease; this reduces or prevents the short column effect. The conclusion can present guidance for the design and construction of masonry-infilled RC frame structure.